THE CONCEPTUAL AND HISTORICAL REVIEW OF CONSTITUTIONAL LAW IN INDONESIA - Indra Muchlis Adnan (Jurnal Pembaharuan Hukum, 2023)
This research discusses constitutional law in Indonesia in terms of concept and history. The position of the constitution is an essential element in a state. It is the basic law in running the government of a country, because every legislation refers to the constitution as a reference. This research uses a qualitative descriptive method with the type of research is a library research. This research led to the conclusion that the constitution affirms the very strong position and relationship between the people and the ruler. The concept of the Constitution in Indonesia is based on the 1945 Constitution. The implementation of Pancasila democracy is based on the constitution or the 1945 Constitution. The history of the development of the Indonesian state administration there are four kinds of constitutions that have been in force, namely first, the period 18 August 1945-27 December 1949; Second, the period 27 December-17 August 1950; third, the period 17 August 1950-5 July 1959 ; fourth, the period 5 July 1959-1998. Â Â